2016
DOI: 10.1002/hbm.23145
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration of the posterior superior temporal sulcus correlates with facial expression recognition

Abstract: Face perception is essential for daily and social activities. Neuroimaging studies have revealed a distributed face network (FN) consisting of multiple regions that exhibit preferential responses to invariant or changeable facial information. However, our understanding about how these regions work collaboratively to facilitate facial information processing is limited. Here, we focused on changeable facial information processing, and investigated how the functional integration of the FN is related to the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…Despite the small overall overlap (Dice coefficient of 0.1), the group activation maps of each imaging technique overlapped at the left pre-central gyrus, which is known to be involved in the processing of face expressions Radua et al, 2010). Although non-overlapping, relevant fMRI and EEG-ESI activations were found at the postcentral sulcus and the posterior superior temporal sulcus (pSTS), the latter being the anchor of the FEPN (Srinivasan et al, 2016;Wang et al, 2016). The concordant activations at (or close to) pSTS are in agreement with our previous work (Direito et al, 2019), and also with a study specifically focused on the functional segmentation of the STS (Deen et al, 2015).…”
Section: Mapping Of Task-specific Brain Network With Eegmentioning
confidence: 97%
“…Despite the small overall overlap (Dice coefficient of 0.1), the group activation maps of each imaging technique overlapped at the left pre-central gyrus, which is known to be involved in the processing of face expressions Radua et al, 2010). Although non-overlapping, relevant fMRI and EEG-ESI activations were found at the postcentral sulcus and the posterior superior temporal sulcus (pSTS), the latter being the anchor of the FEPN (Srinivasan et al, 2016;Wang et al, 2016). The concordant activations at (or close to) pSTS are in agreement with our previous work (Direito et al, 2019), and also with a study specifically focused on the functional segmentation of the STS (Deen et al, 2015).…”
Section: Mapping Of Task-specific Brain Network With Eegmentioning
confidence: 97%
“…Traditional FC analysis measures the correlations of signals within 5 minutes or more, with an assumption that the FC remains constant during the observation period [Biswal et al, ; Fox et al, ; Wang et al, ]. Based on this hypothesis, one can obtain a static pattern of brain activity coherence, which is essentially an average connectivity over the whole period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous neuroimaging studies have demonstrated that the pSTS also plays a vital role in social perception, which refers to the ability to recognize, manipulate, and behave with respect to socially relevant information (Jack & Morris, 2014;Lee, Gao, & McCarthy, 2014;Lieberman, 2007). The pSTS is also thought to be a key region in dynamic facial processing, such as changes in expression and gaze, which are important for social interactions (Engell & Haxby, 2007;Flack et al, 2015;Pelphrey, Morris, & McCarthy, 2004;Wang, Song, Zhen, & Liu, 2016). As a variety of studies have shown, the pSTS is more likely to be activated when both visual and auditory information are presented, whether they are related to speech processing or not (Beauchamp, Lee, Argall, & Martin, 2004;Hocking & Price, 2008;Watson, Latinus, Charest, Crabbe, & Belin, 2014).…”
mentioning
confidence: 99%